Financial Disturbances and Depressions: The View from Economic History - Richard Sylla (Levy Economics Institute of Bard College, 1991)
Events of the past quarter century have renewed the interest of economic historians in major financial disturbances. The study of financial crises was common before World War II, but for the next quarter century little fresh work was done in the area. The chief exception was J. K. Galbraith's The Great Crash. 1929 (1954). Then came M. Friedman and A. J. Schwartz's Monetarv History of the United States. 1867-1960 (1963) with its bold analysis of the great contraction of 1929-1933. Just as that analysis was gaining the attention of economic historians, the United States began to experience credit crunches, steeply rising interest rates, bank failures, debt crises, and a host of other financial disturbances the likes of which had not been seen for a good long time. Soon C. P. Kindleberger's widely read book, Manias. Panics. and Crashes–A Historv of Financial Crises (1978) reminded economic historians and others of the long history of such disturbances. My assignment here, from H. Minsky, is to review what economic historians, especially in recent years, have had to say about financial disturbances and depressions. I inferred from discussions with Prof. Minsky and from some familiarity with his own work that he very much wanted to tie together the two concepts, financial disturbance and depression. The "It" in his book, Can "It Can Happen Again" (1982) is, it will be recalled, a Great Depression. In Minsky's work, a Great Depression results from a debt deflation or, in other words, from an extreme form of t he financial instability that he and others regard as inherent in a capitalist economic system.
Keywords: 330